[Memo from Samuel D. Chilchote, Jr. (Pres. Tobacco Institute) to Executive Committee regarding attached Analysis of the Federal Excise Tax and Tariff Proposals in the Senate Finance Committee Markup] - SAMUEL D. CHILCOTE JR. (Tufts Archival Research Center, 2007)
Memo from Samuel D. Chilchote, Jr. (Pres. Tobacco Institute) to members of the Executive Committee, April 7, 1986 attached to Analysis of the Federal Excise Tax and Tariff Proposals in the Senate Finance Committee Markup. Opposes elimination of deduction of excise taxes for businesses. Argues proposed increase in excise taxes would be borne disproportionately by low income households.